Structural-functionalism redux: adaptation to climate change and the challenge of a science-driven policy agenda. Issue 4 (2nd October 2017) - Wellstead, Adam; Howlett, Michael; Rayner, Jeremy
ABSTRACT: Most efforts to develop a comprehensive, science-based approach to climate change adaptation have been written by natural scientists and resource managers and have adopted an underlying conception of policy-making as a functional process of mutual adjustment between elements of tightly linked natural and social systems. The influence of this framing is especially clear in the popularity of key metaphors such as 'stress, ' 'barriers, ' 'vulnerability, ' and 'resilience.' There are obvious advantages to this way of proceeding, not least the possibility of using the systems concept as an overarching framework to integrate the multidisciplinary teams of researchers commonly employed in large-scale assessments of climate change impacts. Nonetheless, this underlying conception of linked natural and social systems presents significant challenges when it comes to moving the ideas found in these strategic documents forward into the world of policy and practice. As the case studies of North American, Australian, and European studies presented here show, the strategic documents themselves are very short on policy analysis, fail to incorporate the impact of institutions and policy legacies into their analyses, and, as a result, favor unfounded or infeasible management prescriptions. As a consequence, adaptation policy itself remains poorly developed in most jurisdictions.